The Thrombophilic Pattern of Different Clinical Manifestations of Venous Thromboembolism: A Survey of 443 Cases of Venous Thromboembolism - Grifoni, Elisa; Marcucci, Rossella; Ciuti, Gabriele; Cenci, Caterina; Poli, Daniela; Mannini, Lucia; Liotta, Agatina Alessandrello; Miniati, Massimo; Abbate, Rosanna; Prisco, Domenico (Seminars in Thrombosis and Hemostasis, 2012)
Although pulmonary embolism (PE) and deep vein thrombosis (DVT) share many risk factors, it is uncertain whether thrombophilic abnormalities may impact differently on the development of these two clinical manifestations of venous thromboembolism (VTE). To give further insight into this issue, we estimated the association of PE with different types of thrombophilia and evaluated whether these abnormalities have a different prevalence in patients presenting with PE, alone or associated with DVT, as compared with those with isolated DVT. In this study 443 consecutive patients with a first episode of VTE and 304 matched healthy controls underwent laboratory screening for thrombophilia, including natural anticoagulants, factor V Leiden and prothrombin G20210A polymorphisms, antiphospholipid antibodies, homocysteine, factor VIII, and lipoprotein(a). Of the 443 patients, 224 patients had isolated DVT, 144 had combined DVT/PE, and 75 had isolated PE. At least one thrombophilic abnormality was detected in 72.8% of DVT, 66% of DVT/EP, and 60% of isolated PE patients. A high prevalence of hyperhomocysteinemia and elevated lipoprotein(a) levels was found in all patients with no significant differences among the three groups. The prevalence of prothrombin G20210A polymorphism and of elevated factor VIII levels was significantly higher in patients with DVT and DVT/PE than in controls, but not in those with isolated PE, whereas factor V Leiden polymorphism was associated with isolated DVT but not with DVT/PE or isolated PE. In conclusion, the thrombophilic burden seems different in isolated PE versus DVT with or without PE, suggesting that PE may encompass a different pathophysiological process of thrombosis to DVT.
Keywords: venous thromboembolism; pulmonary embolism; thrombophilia